Factors influencing pottery industry in peninsular Malaysia / Faeza Ahmed Ali Al-Dhamari - Al-Dhamari, Faeza Ahmed Ali (2014)

(untitled)
This study has been conducted to investigate the impact of market status, government’s initiatives, economic, social, ritual, and ecological factors, which fall into socio-economic and socio-culture trends, on the artistic quality of pottery production and the performance of potters. Thus, the present study aims to: (1) identify the influence of potters’ characteristics such as gender, and marital status on selected types and techniques used in the pottery production. (2) to determine the impact of selected potters’ characteristics (i.e., age, ethnic/race, career affiliation, and the regional differences) on different types and techniques used in the pottery production. (3) Finally, to predict a set of factors which are presumed to have an impact on the pottery production. A quantitative method is employed to conduct this research by interviewing and distrubting self-administrated questionnaires in order to collect the information and data. Additionally, it is followed by “non-probability-judgmental” sampling as a technique. The technique of selecting samples has been limited to seven states in the Malay Peninsula. The two versions of questionnaires -English and Malay, were distributed upon the targeted population. They were 500 responses obtained. The units of samples were categorized as: (1) government sectors. (2) semi-government manufacturers. (3) private companies and/or individual outlets. The data analysis was conducted based on the following types of statistical tests, the T.Test, and one-way ANOVA. Additionally, Partial Least Square (PLS) software has been chosen to predict the extent of socio-economic and socio-culture impact of factors on certain types and techniques of pottery. The findings of the current study have indicated that, with respect to gender, there is a significant difference in different groups of potters, who are involved in iv certain types of pottery. This variance can be observed significantly in only groups of potters, who are using machines for certain techniques of pottery production. It is found that marital status has an influence on various groups of potters, with respect to certain techniques of pottery. In terms of ANOVA test, the results have shown that, there is a variance in age, and race of potters’ groups in both types and techniques of pottery production. However, the aspect of career affiliation in different groups of potters has differed significantly in some selected types of pottery. In contrast, the techniques selected by potters did not vary significantly with career affiliation. Concerning the regional differences, it is found that, potters from different regions have produced different types of pottery.There has been no significant difference with respect to certain techniques of pottery production. The results of Partial Least Squared have indicated that, the socio-economic factors have highly influenced the types and techniques of pottery production. On the other hand, the socio-culture factors that fall under social and ritual factors have influenced equally all types, and techniques of pottery production. Based on the findings, the proposed structural model can determine the influence of various potters’ characteristics on the pottery production. Moreover, this model could be used to identify market status, government’s initiative, economic, social, ritual, and factors. Such factors could be also utilized as a guide for future studies in other realted fileds.